2004
DOI: 10.1029/2003jd003909
|View full text |Cite
|
Sign up to set email alerts
|

CHAMP and SAC‐C atmospheric occultation results and intercomparisons

Abstract: The German Challenging Minisatellite Payload (CHAMP) and Argentine Satelite de Aplicaciones Cientificas‐C (SAC‐C) Earth science missions, launched in 2000, carry a new generation of Global Positioning System (GPS) receivers for radio occultation sounding of the ionosphere and neutral atmosphere. Though the occultation concept for obtaining profiles of atmospheric temperature, pressure, and moisture was proven in 1995 with GPS/MET, concurrent measurements from CHAMP and SAC‐C present the first opportunity for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
287
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(322 citation statements)
references
References 32 publications
12
287
0
Order By: Relevance
“…11, 2001 and provides RO data continuously in an operational manner since mid-2001 [Wickert et al, 2005]. The amount of data from SAC-C has varied over the last years [Hajj et al, 2004]. Thus, SAC-C data are only available for this study from August -October 2001 and March-November 2002.…”
Section: Introductionmentioning
confidence: 99%
“…11, 2001 and provides RO data continuously in an operational manner since mid-2001 [Wickert et al, 2005]. The amount of data from SAC-C has varied over the last years [Hajj et al, 2004]. Thus, SAC-C data are only available for this study from August -October 2001 and March-November 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Foelsche et al, Observing climate with radio occultation data from the CHAMP satellite, submitted to Climate Dynamics, 2006, hereinafter referred to as Foelsche et al, submitted manuscript, 2006]. First of all, the validity of these climatologies depends on the reliability of the measurements and its retrieval [e.g., Hajj et al, 2004;Wickert et al, 2004], but it also depends on sampling time and location resulting in the sampling error (Foelsche et al, submitted manuscript, 2006). This paper focuses on the sampling error for single LEO satellites, in particular on the effect of local times at which the RO profiles have been taken.…”
Section: Introductionmentioning
confidence: 99%
“…The technique for sounding the Earth's atmosphere was demonstrated by the proof-of-concept GPS Meteorology (GPS/MET) experiment in 1995-1997 (Ware et al 1996). Following GPS/MET, additional missions, that is, the Challenging Minisatellite Payload (CHAMP; Wickert et al 2001) and the Satellite de Aplicaciones Cientificas -C (SAC-C; Hajj et al 2004), have confirmed the potential of RO sounding of the ionosphere, stratosphere, and troposphere. The FORMOSAT-3/COSMIC (Rocken et al 2000) also applies this technique, with primary scientific goal to demonstrate the value of near-real-time RO observations in operational numerical weather prediction, including space weather science and operations.…”
Section: Introductionmentioning
confidence: 96%